INORGANIC STATUS OF TUBERS OF HABENARIA LONGICORNICULATA J.GRAHAM - T. DANGAT, BHAURAV; V. GURAV, RAJARAM (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Habenaria longicorniculata J.Graham is distributed throughout Western Ghats of peninsular India and Srilanka. Tubers of this terrestrial orchid are used as folk remedy and also eaten by some local tribes. Hence an attempt is done to evaluate mineral composition of this orchid. Mineral analysis was done by following standard method of acid digestion. In present study fourteen minerals are analysed for their content in tubers. Phosphorus is present in higher amount as compare to other minerals while Magnesium is lowest In case of trace elements Ferrous is found to be higher and Molybdenum is found to be low in quantity. Present study reveals that tuber of this orchid are good source of minerals and they can be used in food preparation by proper processing, results proves that undoubtedly it's a folk medicine. Further study on this and other orchids needs to be carried out to know the full potential in regards of its medicinal value Keywords: Habenaria, folk medicine, minerals, orchidaceae.